Is Climate Finance Causing Species Extinctions? Incorporating Whack-a-Mole Effects into Synergies Research - Cashore, Benjamin William (2022)
Challenges and solutions for climate cooperation through to 2050: workshop on mature and emerging issues for global climate governance